Design, synthesis and biological evaluation of novel (E)-2-benzylidene-N-(3-cyano-4, 5, 6, 7-tetrahydrobenzo[b]thiophen-2-yl)hydrazine-1-carboxamide derivatives as α-glucosidase inhibitors. (15th November 2021) - Zhang, Jin-He; Xie, Hong-Xu; Li, Yue; Wang, Kai-Ming; Song, Zhiling; Zhu, Kong-Kai; Fang, Lei; Zhang, Juan; Jiang, Cheng-Shi
Graphical abstract: Abstract: In this present study, a series of novel ( E )-2-benzylidene- N -(3-cyano-4, 5, 6, 7-tetrahydrobenzo[ b ]thiophen-2-yl)hydrazine-1-carboxamide derivatives against α-glucosidase were designed and synthesized, and their biological activities were evaluated in vitro and in vivo . Most of the designed analogues exhibited better inhibitory activity than the marketed acarbose, especially the most potent compound 7 with an IC50 value of 9.26 ± 1.84 μM. The direct binding of 7 and 8 with α-glucosidase was confirmed by fluorescence quenching experiments, and the kinetic and molecular docking studies revealed that 7 and 8 inhibited α-glucosidase in a non-competitive manner. Cytotoxicity bioassay indicated compounds 7 and 8 were non-toxic towards LO2 and HepG2 at 100 μM. Furthermore, both compounds were demonstrated to have in vivo hypoglycemic activity by reducing the blood glucose levels in sucrose-treated rats.